Dark respiration rates are not determined by differences in mitochondrial capacity, abundance and ultrastructure in C4 leaves. (6th February 2022) - Fan, Yuzhen; Scafaro, Andrew P.; Asao, Shinichi; Furbank, Robert T.; Agostino, Antony; Day, David A.; von Caemmerer, Susanne; Danila, Florence R.; Rug, Melanie; Webb, Daryl; Lee, Jiwon; Atkin, Owen K.
Abstract: Our understanding of the regulation of respiration in C4 plants, where mitochondria play different roles in the different types of C4 photosynthetic pathway, remains limited. We examined how leaf dark respiration rates ( R dark ), in the presence and absence of added malate, vary in monocots representing the three classical biochemical types of C4 photosynthesis (NADP‐ME, NAD‐ME and PCK) using intact leaves and extracted bundle sheath strands. In particular, we explored to what extent rates of R dark are associated with mitochondrial number, volume and ultrastructure. Based on examination of a single species per C4 type, we found that the respiratory response of NAD‐ME and PCK type bundle sheath strands to added malate was associated with differences in mitochondrial number, volume, and/or ultrastructure, while NADP‐ME type bundle sheath strands did not respond to malate addition. In general, mitochondrial traits reflected the contributions mitochondria make to photosynthesis in the three C4 types. However, despite the obvious differences in mitochondrial traits, no clear correlation was observed between these traits and R dark . We suggest that R dark is primarily driven by cellular maintenance demands and not mitochondrial composition per se, in a manner that is somewhat independent of mitochondrial organic acid cycling in the light. SUMMARY STATEMENT: We found distinct anatomical, ultrastructural and functional differences in mitochondria of leaves using the three classical biochemical types of C4 photosynthesis. Such differences reflect the roles of mitochondria in photosynthesis. However, we found no clear correlation between mitochondrial composition and leaf dark respiration rates, suggesting leaf dark respiration is likely driven by cellular maintenance demands but not mitochondrial composition.